Faktor-Faktor yang Berpengaruh Terhadap Pencegahan Kecurangan di RSUD Kelas B Kabupaten Sukabumi - Kurniawan, Ridwan; Eff, Aprilita Rina Yanti; Rini, Tjipto (Dinasti Research, 2025)
Fraud or fraudulent behavior at Sukabumi Regional General Hospital is reflected in claims for two or more diagnoses that should be included in a single service package in the same episode to obtain a larger claim value in a single patient care episode. The purpose of this study is to provide solutions to efforts to improve fraud prevention by improving factors such as the effectiveness of internal control, clinical pathway compliance, and building good clinical governance. The study used a quantitative design that analyzes the causal influence along with descriptive analysis using the three-box method. Respondents consisted of 180 hospital staff consisting of nurses and doctors. The sampling method used was purposive sampling. The data analysis method used was the PLS-SEM. The results of the study indicate that the effectiveness of internal control, clinical pathway compliance, and clinical governance simultaneously influence fraud prevention. The effectiveness of internal control, clinical pathway compliance, and clinical governance each have a positive effect on fraud prevention. The effectiveness of internal control and clinical pathway compliance each have a positive effect on clinical governance. A comprehensive evaluation of budget management is needed, especially in areas that have the potential for waste. Efficiency efforts need to be supported by thorough budget planning, the use of financial information systems, and increased accountability of each work unit in the use of operational funds.